Membentuk Generasi Unggul Melalui Pendidikan Islam Anak Usia Dini: Peran Ibu Yang Berkualitas - Rahayu, Evi; Maghfiroh, Shofia; Guswanti, Nelia; Seprya, Roby; Puspita, Yenda; Ramadhan, Syahri (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2024)
This community service aims to provide an understanding of the role of mothers to their children regarding how to educate, set an example and accompany each stage of a child's development. This research was carried out using the PAR (Participatory Action Research) method, which involves researchers and participants in collaboration to encourage active participation, feedback and joint knowledge creation. One proof of the transformational power of this training is the fact that the community recognizes how the training has changed their understanding of the very important role of a qualified mother in child development. One of the main results of this community service is that all participants can understand what we have conveyed, the participants are enthusiastic in taking part in the activity by asking questions so that this proves that the participants want to know more about the role of a qualified mother, such as What